Genotypic variation in response to salinity in a new sexual germplasm of Cenchrus ciliaris L. - Quiroga, Mariana Paola; Tommasino, Exequiel Arturo; Griffa, Sabrina Mariana; Ribotta, Andrea Noemi; Lopez Colomba, Eliana; Carloni, Edgardo José; Grunberg, Karina (2017)
As part of breeding program for new salt- tolerant sexual genotypes of Cenchrus ciliaris L., we evaluated the salt- stress response of two new sexual hybrids, obtained by controlled crosses, at seedling and germination stages.